QUALITATIVE INSIGHT INTO FACTORS OF ENROLLMENT IN MILITARY HIGHER EDUCATION INSTITUTIONS IN THE REPUBLIC OF SERBIA - Petrović, Aleksandar; Radojević, Slobodan (The Policy of National Security, 2025)
This paper explores the factors that influenced the decisions of cadets at the Military Academy (MA) and the Faculty of Medicine at the Medical Military Academy (MF MMA) to enroll in military higher education institutions (HEIs) in the Republic of Serbia. The research aimed to identify, through qualitative analysis of focus group responses, the reasons and motives behind cadets’ enrollment decisions and their reflections on those decisions. The theoretical framework of this paper is based on empirical research findings and theoretical considerations regarding the factors and models of HEI selection applicable to both civilian and military contexts. The research was conducted on a sample of 32 cadets, and the data were sorted and analyzed through ten thematic categories. The results reveal that the decision of cadets to enroll in military HEIs in the Republic of Serbia was shaped by a complex mix of social, institutional, and economic factors, many of which have already been identified in relevant scientific literature. The insights gained from this study can provide a foundation for developing an instrument for future quantitative research and refining higher education institutions’ communication strategies.
Keywords: Military Academy; Faculty of Medicine of the Military Medical Academy; cadets; HEI choice; military profession; focus group